Xenorhabdus lircayensis sp. nov., the symbiotic bacterium associated with the entomopathogenic nematode Steinernema unicornum. Issue 12 (13th December 2021) - Castaneda-Alvarez, Carlos; Prodan, Simona; Zamorano, Alan; San-Blas, Ernesto; Aballay, Erwin
Abstract : Xenorhabdus is a symbiotic group of bacteria associated with entomopathogenic nematodes of the family Steinernematidae. Although the described Steirnernema species list is extensive, not all their symbiotic bacteria have been identified. One single motile, Gram-negative and non-spore-forming rod-shaped symbiotic bacterium, strain VLS T, was isolated from the entomopathogenic nematode Steinernema unicornum . Analyses of the 16S rRNA gene determined that the VLS T isolate belongs to the genus Xenorhabdus, and its closest related species is Xenorhabdus szentirmaii DSM 16338 T (98.2 %). Deeper analyses using the whole genome for phylogenetic reconstruction indicate that VLS T exhibits a unique clade in the genus. Genomic comparisons considering digital DNA–DNA hybridization (dDDH) values confirms this result, showing that the VLS T values are distant enough from the 70 % threshold suggested for new species, sharing 30.7, 30.5 and 30.3 % dDDH with Xenorhabdus khoisanae MCB, Xenorhabdus koppenhoeferi DSM 18168 T and Xenorhabdus miraniensis DSM 18168 T, respectively, as the closest species. Detailed physiological, biochemical and chemotaxonomic tests of the VLS T isolate reveal consistent differences from previously described Xenorhabdus species. Phylogenetic, physiological, biochemical and chemotaxonomic approaches show that VLS T represents a new species of the genus Xenorhabdus, for which the name Xenorhabdus lircayensis sp. nov. (type strain VLS T =CCCT 20.04 T =DSM 111583 T ) is proposed.